First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Systematic conservation prioritization with the prioritizr R package - Jeffrey O. Hanson; Richard Schuster; Matthew Strimas‐Mackey; Nina Morrell; Brandon P. M. Edwards; Peter Arcese; Joseph R. Bennett; Hugh P. Possingham (Conservation Biology, 2025)
Plans for expanding protected area systems (prioritizations) need to fulfill conservation objectives. They also need to account for other factors, such as economic feasibility and anthropogenic land‐use requirements. Although prioritizations are often generated with decision support tools, most tools have limitations that hinder their use for decision‐making. We outlined how the prioritizr R package ( https://prioritizr.net ) can be used for systematic conservation prioritization. This decision support tool provides a flexible interface to build conservation planning problems. It can leverage a variety of commercial (e.g., Gurobi) and open‐source (e.g., CBC and SYMPHONY) exact algorithm solvers to identify optimal solutions in a short period. It is also compatible with a variety of spatially explicit (e.g., ESRI Shapefile, GeoTIFF) and nonspatial tabular (e.g., Microsoft Excel Spreadsheet) data formats. Additionally, it provides functionality for evaluating prioritizations, such as assessing the relative importance of different places selected by a prioritization. To showcase the prioritizr R package, we applied it to a case study based in Washington state (United States) for which we developed a prioritization to improve protected area coverage of native avifauna. We accounted for land acquisition costs, existing protected areas, places that might not be suitable for protected area establishment, and spatial fragmentation. We also conducted a benchmark analysis to examine the performance of different solvers. The prioritization identified 12,400 km 2 of priority areas for increasing the percentage of species’ distributions covered by protected areas. Although open source and commercial solvers were able to quickly solve large‐scale conservation planning problems, commercial solvers were required for complex, large‐scale problems.. The prioritizr R package is available on the Comprehensive R Archive Network (CRAN). In addition to reserve selection, it can inform habitat restoration, connectivity enhancement, and ecosystem service provisioning. It has been used in numerous conservation planning exercises to inform best practices and aid real‐world decision‐making.

Co-occurrence of biodiversity, carbon storage, coastal protection, and fish and invertebrate production to inform global mangrove conservation planning - Michael Sievers; Christopher J. Brown; Jennifer McGowan; Mischa P. Turschwell; Christina A. Buelow; Briana Holgate; Ryan M. Pearson; Maria F. Adame; Dominic A. Andradi-Brown; Andy Arnell; Brendan G. Mackey; Philine S.E. zu Ermgassen; et al. (Science of The Total Environment, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Mitochondrial SIRT3 Deficiency Results in Neuronal Network Hyperexcitability, Accelerates Age-Related Aβ Pathology, and Renders Neurons Vulnerable to Aβ Toxicity - Isabella Perone; Nathaniel Ghena; Jing Wang; Chelsea Mackey; Ruiqian Wan; Sulochan Malla; Myriam Gorospe; Aiwu Cheng; Mark P. Mattson (NeuroMolecular Medicine, 2023)

Correction to: Coastal flood risk within a peri‑urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2022)

Coastal flood risk within a peri-urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Speleothem and glacier records of latest Pleistocene–early Holocene climate change in the western North American interior - Brendon J. Quirk; Glen N. Mackey; Diego P. Fernandez; Andy Armstrong; Jeffrey R. Moore (Journal of Quaternary Science, 2020)
Rapid and high‐magnitude North Atlantic climate oscillations following the Last Glacial Maximum have been correlated to climate change events in western North America. However, the strength of teleconnections between the North Atlantic and the interior of western North America remains poorly understood. We present a U‐series calibrated speleothem record from Timpanogos Cave National Monument, located at 2040 m asl in the Wasatch Mountains of Utah, spanning 13.5–10.6 ka. Additionally, we carried out a climate reconstruction for a coeval glacier advance in the Wind River Range of Wyoming. Our results indicate that between 13.5 and 12.8 ka, the Wasatch was probably first cool and dry and then warmed. After 12.8 ka, our record suggests cool and/or wetter conditions followed by reduced moisture until 11.8 ka, followed by an early Holocene wet period. The Timpanogos record exhibits few similarities with those from the North Atlantic. Climate reconstructions of the Titcomb Basin glacier suggest modest temperature depressions relative to modern ( 150%). The high‐altitude speleothem record presented here provides a valuable basis for understanding latest Pleistocene–early Holocene glacial episodes in western North America.

Equilibrium, Kinetic and Optimization Studies for the Adsorption of Tartrazine in Water onto Activated Carbon from Pecan Nut Shells - J. Torres-Pérez; Y. Huang; P. Hadi; H. Mackey; Gordon McKay (Water, Air, & Soil Pollution, 2018)

In vivo neuroimaging and behavioral correlates in a rat model of chemotherapy-induced cognitive dysfunction - Robert L. Barry; Nellie E. Byun; M. Noor Tantawy; Chase A. Mackey; George H. Wilson; Adam J. Stark; Michael P. Flom; Laura C. Gee; C. Chad Quarles (Brain Imaging and Behavior, 2018)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Greater preference consistency during the Willingness-to-Pay task is related to higher resting state connectivity between the ventromedial prefrontal cortex and the ventral striatum - Scott Mackey; Valur Olafsson; Robin L. Aupperle; Kun Lu; Greg A. Fonzo; Jason Parnass; Thomas Liu; Martin P. Paulus (Brain Imaging and Behavior, 2016)

Structural dynamic analysis of the epicentral zone of the Ilin-Tas earthquake (Feb 14, 2013, Ms = 6.9) - L. P. Imaeva; B. M. Koz’min; V. S. Imaev; K. G. Mackey (Journal of Seismology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Diel cycling of DNA staining and nifH gene regulation in the unicellular cyanobacterium Crocosphaera watsonii strain WH 8501 (Cyanophyta) - Kory Pennebaker; Katherine R. M. Mackey; Rachelle M. Smith; Stanly B. Williams; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary Crocosphaera watsonii WH 8501 is a marine unicellular cyanobacterium that fixes nitrogen primarily during the dark phase of a light–dark (LD) cycle. Circadian clocks modulate gene transcription and cellular activity in many, if not all, cyanobacteria. A model for circadian control has been proposed in cyanobacteria, called the oscilloid model, which is based on topological changes of nucleoid DNA which in turn regulates gene transcription. In this study, the marine unicellular diazotrophic cyanobacteria C. watsonii WH 8501 and Cyanothece sp. ATCC 51142 were found to have daily fluctuations in DNA staining using Hoechst 33342 and SYBR I Green fluorescent dyes. Up to 20‐fold decreases in DNA fluorescence of Hoechst‐stained cells were observed during the dark phase when cultures were grown with a 12:12 LD cycle or under continuous light (LL). The variation in DNA staining was consistent with changes in DNA topology proposed in the oscilloid model. The abundance of nifH transcripts in C. watsonii WH 8501 was rhythmic under LD and LL cycles, consistent with a circadian rhythm. Cycles of DNA fluorescence and photosynthetic efficiency were disrupted when cultures were shifted into an early dark phase; however, nifH transcripts predictably increased in abundance following the premature transition from light to darkness. Thus, nifH gene expression in C. watsonii WH 8501 appears to be influenced by both circadian and environmental factors.

Novel quantitative trait loci for central corneal thickness identified by candidate gene analysis of osteogenesis imperfecta genes - David P. Dimasi; Jern Y. Chen; Alex W. Hewitt; Sonja Klebe; Richard Davey; John Stirling; Elizabeth Thompson; Robin Forbes; Tiong Y. Tan; Ravi Savarirayan; David A. Mackey; Paul R. Healey; et al. (Human Genetics, 2010)

Major Conservation Policy Issues for Biodiversity in Oceania - R. T. KINGSFORD; J. E. M. WATSON; C. J. LUNDQUIST; O. VENTER; L. HUGHES; E. L. JOHNSTON; J. ATHERTON; M. GAWEL; D. A. KEITH; B. G. MACKEY; C. MORLEY; H. P. POSSINGHAM; et al. (Conservation Biology, 2009)
Oceania is a diverse region encompassing Australia, Melanesia, Micronesia, New Zealand, and Polynesia, and it contains six of the world's 39 hotspots of diversity. It has a poor record for extinctions, particularly for birds on islands and mammals. Major causes include habitat loss and degradation, invasive species, and overexploitation. We identified six major threatening processes (habitat loss and degradation, invasive species, climate change, overexploitation, pollution, and disease) based on a comprehensive review of the literature and for each developed a set of conservation policies. Many policies reflect the urgent need to deal with the effects of burgeoning human populations (expected to increase significantly in the region) on biodiversity. There is considerable difference in resources for conservation, including people and available scientific information, which are heavily biased toward more developed countries in Oceania. Most scientific publications analyzed for four threats (habitat loss, invasive species, overexploitation, and pollution) are from developed countries: 88.6% of Web of Science publications were from Australia (53.7%), New Zealand (24.3%), and Hawaiian Islands (10.5%). Many island states have limited resources or expertise. Even countries that do (e.g., Australia, New Zealand) have ongoing and emerging significant challenges, particularly with the interactive effects of climate change. Oceania will require the implementation of effective policies for conservation if the region's poor record on extinctions is not to continue .

Evidence for a novel glaucoma locus at chromosome 3p21-22 - Paul N. Baird; Simon J. Foote; David A. Mackey; Jamie Craig; Terence P. Speed; Alexandre Bureau (Human Genetics, 2005)

Elemental Composition of Liver and Kidney Tissues of Rough-Toothed Dolphins ( Steno bredanensis ) - E. A. Mackey; R. D. Oflaz; M. S. Epstein; B. Buehler; B. J. Porter; T. Rowles; S. A. Wise; P. R. Becker (Archives of Environmental Contamination and Toxicology, 2003)

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

Zipping up transcription factors: Rational design of anti-Jun and anti-Fos peptides - Naresh P. S. Bains; Jackie A. Wilce; Katja H. Heuer; Mark Tunstall; Joel P. Mackey; Max R. Bennett; Anthony S. Weiss; Glenn F. King (International Journal of Peptide Research and Therapeutics, 1997)

Bioaccumulation of vanadium and other trace metals in livers of Alaskan cetaceans and pinnipeds - E. A. Mackey; P. R. Becker; R. Demiralp; R. R. Greenberg; B. J. Koster; S. A. Wise (Archives of Environmental Contamination and Toxicology, 1996)

Bioaccumulation of Vanadium and Other Trace Metals in Livers of Alaskan Cetaceans and Pinnipeds - E. A. Mackey; P. R. Becker, R. Demiralp; R. R. Greenberg; B. J. Koster; S. A. Wise (Archives of Environmental Contamination and Toxicology, 1996)